Sistemic Citrobacter Freundii infection in carp - Jeremić Svetlana; Jakić-Dimić Dobrila (Veterinarski Glasnik, 2003)
The paper describes ta clinical disease in carp fish species which indicated a typical acute bacterial septicemia caused by the gram-negative bacteria Citrobacter freundii. An unusual mortality of carp fish species was observed during low water temperatures at the beginning of the year. A total of 39 samples were taken for laboratory examinations from diseased fish which had become darker, with expressed exophthalmus bleedings on the skin and eyes and 10 samples from clinically healthy fish. Part of the altered organs gills, parenchymatous organs and intestines were used for isolating the causes. The usal methods of bacteriological examinations were used for the investigations. Cultures were identified by examining key phenotype markings and using an Api 20E system as Citrobacter freundii. Other parts of parenchymatous organs and intestines were fixed in 10% formaline prepared according to the standard histological method. Pathohistological examinations established inflammatory and necrotic changes in internal organs. We succeeded in reproducing the disease with an artificial infection using a pure culture of Citrobacter freundii. This is the first published report on establishing Citrobacter freundii as the cause of carp diseases in Serbia.